Characterization of Patients with Parkinson’s Disease: A 3-year follow-Up Study in Malaysia - Edeltraud B. Zulema X. (Open Journal of Physicians and Surgeons, 2025)
Background: Parkinson's disease (PD) is a progressive disorder of the nervous system resulting in degeneration of the patient. We aim to evaluate PD patients clinical characteristics, disease progression and clinic outcomes in George Town, Malaysia for over a period of 3 years. Objective: To examine the characteristics of PD patients, and the clinical and non-clinical management strategies, disease progression and outcomes after a 3 year follow up. Methodology: This was a multicenter longitudinal cohort study to be conducted at a tertiary healthcare center in George Town, Malaysia between the period of January 2022 - December 2024. The sample will include 200 patients diagnosed with PD according to the UK Parkinson's Disease Society Brain Bank criteria. Demographic data, symptoms of clinical diseases, treatment and disease progression were assessed through interview at initial stage and followed up for 03 years. The UPDRS and Hoehn and Yahr staging were used to assess the severity of the disease. Statistical analysis was performed using descriptive and inferential methods. Results: Participants were aged 65.4 ± 8.2 years with a gender distribution of 1.5:1 of male to female. The triad of tremor (78%), bradykinesia (65%) and rigidity (58%) remained the most predominant symptoms. During the three year follow up, it was noted that 62% of the patients experienced disease progression with the mean change of 12.5 points in the UPDRS scale, While on the other hand, motor complications such as dyskinesias and fluctuations were noted in 45% of the patients. Majority of the patients took Levodopa , which was 85% of total medication and other included dopamine therapy (40%) and MAO-B therapy (25%). Within the scope of this study the results of the PDQ-39 scale indicated that over the study period the quality of life of patients rapidly declined (p < 0.001). Conclusion: Prompt and accurate diagnosis followed by optimally structured treatment is needed to address the motor and non motor symptoms to improve the quality of life in the patients. The results quite similarly justify the need for integrated care approaches and long term follow ups for PD care in Southeast Asian countries.